Orgulho, luta e resistência : uma análise antropológica da parada LGBT de Sergipe - Passos, Gladston Oliveira dos (2022)
Sergipe's LGBT Parade is the result of the engagement of NGOs, activists and individual activists who demand improvements for the LGBTQIA+ population. Its existence is a result of the struggle of the homosexual movement that existed in the capital since the 1980s. Over two decades the LGBT Parade has become a tool for confronting prejudice, pointing out rights that are neglected by the State. It is also through the Parade that the LGBTQIA+ community feels empowered and represented to make demands to the public power and denounce the violence suffered on a daily basis. The Parade is the moment in which these people experience forms of freedom to demonstrate who they are in their fullness and consequently to be proud of their gender identity or sexual orientation. For many years, gays, lesbians, transvestites and transsexuals have suffered from a lack of visibility because they were prevented from coming out in their living spaces, the result of a macho, heteronormative, and prejudiced culture. In the search for a cultural change, several NGOs, collectives and individual activists got together in the construction of this event that lasts until today. During the planning and execution of the Parade, disagreements arise, causing tensions and conflicts among those involved. Thus, the present dissertation aims to analyze how the power relations that constitute the construction of the Sergipe LGBT Parade are presented. The methodological path of the work involved bibliographic research, consulting newspapers and interviews. From this analysis, we can see that the Parade is built with a lot of dialogue between the parties involved, but there are also many divergences in positions, especially political ones on the part of some coordinators and supporters of the event. Such attitudes end up resulting in the rupture of partnerships between institutions and/or between militants, either temporarily or permanently.